2018
DOI: 10.4067/s0717-95022018000100109
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Endothelin-1 and Ki-67 in Normotensive and Severe Preeclamptic Placentas

Abstract: EKINCI, A.; AKTAS, A.; DÖNDER, A.; EKINCI, C., TURGUT, A.; DEVECI, S. & DEVECI, E. Expression of endothelin-1 andKi-67 in normotensive and severe preeclamptic placentas. Int. J. Morphol., 36(1):109-112, 2018. SUMMARY:Severe preeclampsia (HELLP syndrome) is a life-threatening pregnancy complication, usually a severe form of preeclampsia. In this study, we aimed to examine histopathologic changes and Endothelin-1 and KI-67 expression levels by immunohistochemical methods in severe preeclamptic placentas. Severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
(7 reference statements)
0
0
0
2
Order By: Relevance
“…In the literature, there are studies showing histopathologic changes caused by COVID-19 infection on both placenta and umbilical cord [12][13] . Apart from covid-19 infection, diseases such as preeclampsia also cause histologic changes in the placenta 14 . While several routes of human-to-human transmission of SARS-CoV-2 have been identified, vertical transmission of infection from mother to fetus remains a valid and unresolved question.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are studies showing histopathologic changes caused by COVID-19 infection on both placenta and umbilical cord [12][13] . Apart from covid-19 infection, diseases such as preeclampsia also cause histologic changes in the placenta 14 . While several routes of human-to-human transmission of SARS-CoV-2 have been identified, vertical transmission of infection from mother to fetus remains a valid and unresolved question.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was found that especially intervillous thrombosis fibril accumulation was prominent in the basal plaque layer and the distribution of lesions related to the degree of invasive subgroups of structures containing large-scale lacunae was significant 10 . Like placenta previa, preeclampsia and covid-19 infection also cause histologic changes in the placenta and umblical cord [11][12][13] .…”
Section: Discussionmentioning
confidence: 99%
“…Centro Universitário de João Pessoa (UNIPÊ), João Pessoa -PB 6. Universidade Presidente Antonio Carlos (UNIPAC), Juiz de Fora -MG 7. Centro Universitário Claretiano (CEUCLAR), Rio Claro -SP 8.…”
unclassified